تطبيق طريقة التعلم بالاكتشاف (Discovery Learning) لترقية قدرة الطلبة على تعلم المفردات العربية - Muhammad Rizki ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2026)
This study aims to improve Arabic listening skills (Maharah Istima’) through the use of Arabic songs among fifth-grade students at Madrasah Ibtidaiyah Ihsaniyah Jambi City. The research employed Classroom Action Research consisting of two cycles, namely planning, action, observation, and reflection. The subjects of this study were 31 students. Data were collected through observation, interviews, documentation, and tests. The findings revealed that the use of Arabic songs created a more interactive and enjoyable learning atmosphere, increased student participation, and improved listening comprehension skills. The average student score increased from 52% in the pre-action stage to 59.5% in the first cycle and reached 72.25% in the second cycle. Learning completeness also improved significantly from 25% in cycle I to 75% in cycle II. Arabic songs helped students recognize vocabulary, understand pronunciation, improve concentration, and reduce anxiety in learning Arabic. Therefore, the use of Arabic songs can be considered an effective and innovative medium for improving listening skills in Arabic language learning at the elementary Islamic school level.